THE ABUNDANCE OF PHYTOPLANKTON IN PONDS OF PEAT SOIL GIVEN DIFFERENT BIOFERTILIZER - Putri, Adlia Tri; Hasibuan, Saberina; ', Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted from August to November 2016, in the peat soil of ponds at Kualu Nenas, Kampar District, Riau Province. Observation of phytoplankton have been done in the Laboratory of Environment Quality of Aquaculture, Aquaculture Department, Fisheries and Marine Faculty. Objective of this study was to determine the best kinds of biofertilizer to increase the abundance of phytoplankton in the peat soil of ponds. Method this research using a Complete Randomized Design (CRD) was one factor with 3 levels of treatment. The kinds of using are P0 (without giving the biofertilizer), P1 (biofertilizer from chicken feses 9,4 kg m-2), P2 (biofertilizer from cow feses 9,4 kg m-2) and P3 (biofertilizer from human feces 9,4 kg m-2). The best of treatment of this research was the P3 (biofertilizer from human feces 9,4 kg m-2). Phytoplankton abundance this treatment is 5.331 individu/L, rather than of the other treatment. The water quality parameters in this research is good, especially of temperature 27-32 0C, pH 5-7, dissolved oxygen 2,7-5,7 mg/L, nitrate 2,54-3,61 ppm and orthoposfat 1,50-2,26 ppm. Then, carbon dioxide is highly 12,90-29,98 mg/L refering for the Quality Standart of Aquaculture.Keywords: Biofertilizer, Azotobacter sp., Phytoplankton, Water quality